Efficient automated synthesis of 2-(5-[18F]fluoropentyl)-2-methylmalonic acid ([18F]ML-10) on a commercial available [18F]FDG synthesis module. (May 2017) - Liu, Shaoyu; Nie, Dahong; Jiang, Shende; Tang, Ganghua
Abstract: [ 18 F]ML-10 (2-(5-[ 18 F]fluoro-pentyl)-2-methylmalonic acid) is a small molecule positron emission tomography (PET) probe for apoptosis imaging. Automated synthesis of [ 18 F]ML-10 was developed by using two different purification methods through a direct saponification procedure on a modified commercial [ 18 F]Fluoro-2-Deoxyglucose ([ 18 F]FDG) synthesizer. C18 purification method 1: The final [ 18 F]ML-10 solution containing ethanol was obtained with radiochemical yields of 60±5% (n=5) at the end of bombardment (EOB) and radiochemical purity of 98% in 35 min. Al2 O3 and SCX purification method 2: To avoid possible side effects of a conventional ethanol-containing formulation, an new ethanol-free solution of [ 18 F]ML-10 was also developed, the radiochemical yields was 50±5% (n=5, EOB) within 45 min and the radiochemical purity was 98%. Highlights: The production of [ 18 F]ML-10 was optimized by using a straightforward saponification procedure. Automated synthesis was performed on a commonly FDG synthesis module. An ethanol-containing [ 18 F]ML-10 formulation was obtained with high radiochemical yield in a shorter time. An ethanol-free formulation method of [ 18 F]ML-10 was also developed.